The Treatment of Fibromyalgia Using Vibrational Herbal Medicine and the Laws of Ancient Wisdom - Eltouny, Almoez LeDin Ellah M. S. (Archives of Clinical and Medical Case Reports, 2018)
This is a case study to determine a treatment and/ or a cure for Fibromyalgia. This was a study and trial on one patient who had been diagnosed with Fibromyalgia in the USA. She had been under medication for Fibromyalgia, but that did not appear to have made a great deal of difference and the patient could control her pain or condition. My work dealt with finding treatments for unusual ailments that could not be cured by conventional methods. The technique of Vibrational Herbal Medicine was discovered by accident, while experimenting with the measurement of Herbs to find out their energy qualities. Our research continued for a few years and the results were published in “Explore Magazine” published in Prescott, Arizona in 2000. We studied what energies affect Blood Pressure, and concentrated heavily on finding a treatment or cure, for Hep. C viral, which was endemic in Egypt, at that time. Our research continued and spread to many other ailments and diseases over the next twenty years. In 2017, we were approached by and acquaintance who was aware of our work and wanted us to take the case of this female patient with Fibromyalgia. It was an intriguing case as I had never treated a similar case. The following is a base on which we came to the technique employed in Vibrational herbal Medicine.